1991
DOI: 10.1002/ssu.2980070607
|View full text |Cite
|
Sign up to set email alerts
|

Surgical treatment of gastric cancer: Retrospective survey of 1,704 operated cases with special reference to total gastrectomy as the operation of choice

Abstract: Total gastrectomy is discussed as the operation of choice among different surgical approaches for gastric carcinoma. We prefer the performance of an elective total gastrectomy with systematic lymphadenectomy (compartments I and II) and obligatory splenectomy. A retrospective study of 1,704 consecutive cases of gastric carcinomas showed a better outcome following total gastrectomy in relationship to distal subtotal gastrectomy, but these results cannot be used as evidence because of the lack of a prospective st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
19
1
1

Year Published

1993
1993
2006
2006

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 43 publications
(22 citation statements)
references
References 35 publications
1
19
1
1
Order By: Relevance
“…In our trial multivariate analysis showed that in pa tients with gastric cancer, stage of disease and adequacy of surgery are the most important prognostic factors affect ing survival and time to progression [44], The influence of disease stage on the prognosis is widely known [45][46][47][48], and advanced stage at diagnosis is probably responsible for poor results obtained in the treatment of gastric cancer in western countries [9][10][11][12]. Inadequate surgery may result in stage shifting, and in compromised radicality of treatment [48].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In our trial multivariate analysis showed that in pa tients with gastric cancer, stage of disease and adequacy of surgery are the most important prognostic factors affect ing survival and time to progression [44], The influence of disease stage on the prognosis is widely known [45][46][47][48], and advanced stage at diagnosis is probably responsible for poor results obtained in the treatment of gastric cancer in western countries [9][10][11][12]. Inadequate surgery may result in stage shifting, and in compromised radicality of treatment [48].…”
Section: Discussionmentioning
confidence: 99%
“…at least in the areas with a high incidence, gastric carcinoma is still a major oncological problem. Surgery is still the main treatment modality for patients with resectable gastric carcinoma, but although the rate of tumor resectability has risen to 80% [9], the 5-year survival of patients treated with surgery alone does not exceed 30% [12,13].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Eine Analyse an 1700 Patienten zeigte, dass die 5-Jahres-Überlebensrate bei Patienten mit lokal fortgeschrittenen Tumoren im Stadium III bei etwa 20% bzw. im Stadium IV mit resektablen Tumoren bei 15% liegt [1]. Patienten mit inoperablen Tumoren haben unbehandelt lediglich eine mediane Lebenserwartung von knapp 3 Monaten.…”
unclassified
“…This is particularly true for gastric carcinoma. Among the estab lished treatment modalities, resection of the tumor repre sents the therapy of choice and offers the only chance for long-term cure [1,2], In the last decades, surgical treat ment of gastric carcinoma has undergone major advances as represented by an increased resectability, a decreased morbidity and mortality and an improvement in overall survival [3][4][5][6]. Irrespective of the extent of resection of the primary tumor by either subtotal or total gastrectomy, the role of lymphadenectomy in surgery for gastric cancer remains controversial [7][8][9][10][11], Already at the beginning of this century, the pioneers of gastric surgery argued for lymph node dissection in case of gastric adenocarcinoma; according to a recent questionnaire in Europe, however, only 27% of the participating institutions are performing systematic lymphadenectomy [12], This result is even more surprising, since numerous retrospective Japanese studies, based on the classification of the various gastric lymph node stations, have repeatedly reported improved survival rates following extended radical lymphade nectomy [8,[13][14][15].…”
Section: Introductionmentioning
confidence: 99%